Update on recurrent vulvovaginal candidiasis. (23rd September 2021) - Borland, Amy; Ovens, Katie; Offiah, Ifeoma; Dua, Anupreet; Freeman, Robert
Abstract : Key Content: Recurrent vulvovaginal candidiasis (RVVC) affects millions of women worldwide. Defined as four or more episodes per year of vulvovaginal candidiasis (VVC), it is a cause of significant morbidity, affecting quality of life, relationships and ability to work. RVVC is uncommon in prepubertal girls and the incidence markedly declines following menopause. Some gynaecologists and trainees have unmet training needs in the optimal assessment and management of RVVC. A multifaceted approach is often required, including vulval skin care, avoidance of triggers and induction and suppression regimes with antifungal drugs. This review combines the current literature on VVC, incorporating data on novel therapies with established standard management protocols. Learning objectives: To be able to assess risk factors and correctly diagnose VVC. To know the current management strategies for RVVC and the efficacy of novel therapies. To be aware of the common differentials of bacterial vaginosis and trichomonas vaginalis and their recommended management.